ANALISIS PERKEMBANGAN NILAI MORAL DAN AGAMA ANAK USIA DINI PADA LINGKUNGAN PEMBELAJARAN MONTESSORI DI KINDY HOUSE - Nunik Kurniawati; Sabrina Tri Rizki; Ida Ermiana (STKIP Subang, 2026)
This study aims to analyze the moral and religious development of young children within the Montessori learning environment at Kindy House. A descriptive qualitative approach was employed. Data were collected through observations of 48 children aged 4–6 years and analysis of Term 4 Child Development Reports (LPA). The observation instrument was developed based on the National Standards of Child Development Achievement (STTPA) for Moral and Religious Values and enriched with indicators from the domains of Religious Values, Character Education, and Social-Emotional Development. The findings showed that most children achieved the categories of Developing as Expected (BSH) and Very Well Developed (BSB). Moral and religious development was reflected through Montessori activities such as Practical Life, Grace and Courtesy, daily routines, Care of Environment, gardening programs, and Birthday Walk. These activities supported the development of responsibility, discipline, empathy, environmental awareness, and gratitude. The study concludes that the Montessori learning environment positively contributes to children’s moral and religious development through meaningful and concrete learning experiences.